Análisis de intervención de las series temporales patrimonio y flujo neto de dinero de los Fondos de Inversión Socialmente Responsables (FISR) de Brasil - Ferruz Agudo, Luis (2011)
The aim of this study is to analyze whether creating an own category for Socially Responsible Investment Funds (FISR) in Brazil generates time series changes in heritage and cash flow of these funds. We studied all FISR Brazilians during the period 2001 to 2009. The methodology used was the Box & Jenkins (1970) and interventions. The results reveal interventions in the two variables; however, the interventions take place before the change of category. Another important conclusion is that the category change does not cause alterations in the time series of the two variables considered.